Thematic analysis of leadership values in apologies - Raja Ravi Varma, Susanna Bithiah Varma; Paramasivam, Shamala (Techmind Research, 2018)
The aim of the study was to elicit leadership values embedded in Obama’s apology speeches to have an insight of his leadership in the face of crisis. During his presidency, Obama had issued a number of successful remedial apologies as an action performed by the offender to calm the angered party, seek forgiveness and achieve reconciliation. The study found that Obama portrayed an array of values such as responsibility, accountability, determination and dedication to duty, trustworthiness and truthfulness, apologetic, regretful, appreciative of sacrifice, visionary, and to comfort and sympathise. This paper gives an insight of how the methodology for the study of leadership values in Obama’s apologies was carried out. The methodology relies on positive discourse analysis and grounded theory for performing a thematic analysis through linguistic coding.